The associations between child behavioral problems, parents’ emotional regulation difficulties, and parental burnout among Israeli parents of children with autism during wartime - Shnitzer-Meirovich, Shlomit; Aviad, Shani; Bechar-katz, Inbal; Araten-Bergman, Tal; Shenaar-Golan, Vered; Gur, Ayelet (Frontiers in Psychology, 2024)
Introduction: Parents of children with Autism Spectrum Disorder (ASD) face heightened challenges during crises like war, leading to parental burnout (PB). Wartime demands may exacerbate the children's behavioral difficulties, which associated with PB. Successful emotional regulation (ER) is considered a protective factor for PB. This study aimed to explore the associations between the child behavioral problems, parent's ER difficulties and PB among parents of children ASD during wartime. Methods: 92 parents completed demographic, Parental Burnout, Difficulties in Emotion Regulation, and Child Aberrant Behavior questionnaires. In addition, 18 parents of children with ASD aged 6-21 were semi-interviewed. Results: During wartime, child behavioral problems and parents' ER difficulties were positively correlated with PB, contributing beyond background characteristics and other changes following the war. Parent ER difficulties serve as a mediation variable and did not function as a moderation variable between child behavioral problems and PB. Discussion: This study emphasizes the increased vulnerability of parents of children with ASD during wartime, highlighting the need for a deeper understanding of how these circumstances affect parental risk and resources. Effective interventions should target emotional regulation and address child behavioral issues, necessitating prioritized support for affected families despite wartime challenges.